Perilaku konsumen pada pembelian beras analog jagung di Kota Gorontalo - Ulfira Ashari; Syamsir Syamsir (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Analog rice is a functional food made from part or all of non-rice ingredients consumed like eating rice in general. One of the analog rice that is widely consumed is corn rice. Consumption of corn rice has become a culture of the people of Gorontalo. The aims of this study were to (1) determine the attributes that influence the purchase decision of corn analog rice in Gorontalo City and (2) analyze consumer attitudes towards the attributes of corn analog rice in Gorontalo City. Method: The research was conducted at the Gorontalo City Central Market, with a total sample of 65 respondents who were selected by accidental sampling. Data analysis used descriptive analysis by making a frequency distribution table to determine the attributes that influence the purchase decision of corn analog rice in Gorontalo City. Multiattribute Fishbein analysis was used to analyze consumer attitudes towards the attributes of corn analog rice. Result: The results showed that the rice analogue of corn that respondents liked was rice with small/fine grain, yellow in color, aromatic, free from dregs, and cheap. After being cooked into rice has a sweet rice taste and fluffier texture. The results of the Fishbein Multi-attribute analysis showed that the quality of rice was ranked first with a score of 20,10 points, followed by the color of the rice with a score of 18,49 points. Conclusion: Attributes that influence the purchase decision of corn analog rice in Gorontalo City include the shape of rice grains, the taste of corn rice, the texture of corn rice, color, aroma, quality, and price of rice. Fishbein's multi-attribute analysis shows that the attributes of quality and color of corn rice are the most important considerations in purchasing corn analog rice.